PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DIVISI MARKETING EIGER ADVENTURE - Mulyani, Sri; Recky, Recky; Muttaqin, Ridlwan; Hendra Saputro, Arie (Komunitas Manajemen Kompetitif, 2026)
Abstract In an era of globalization and digitalization that continues to develop, companies need to have employees who are able and can adapt to change. The role of employees, especially in marketing, is very important because they are an important driver in creating added value and maintaining the company's image in the eyes of customers. In recent years, EIGER Adventure has experienced changes in increasingly complex business dynamics, especially in the marketing division which serves as the front line in maintaining the company's good name in the midst of increasingly fierce competition in the outdoor retail industry. What can be seen is a mismatch between the targets set by the company and the real work of some marketing employees. This study uses a quantitative design with a survey approach, because this design allows researchers to test the relationships between variables objectively and measurably. The research method used is a survey method with a questionnaire as the main instrument. Leadership Style has a significant effect on the Performance of Eiger Adventure Marketing Division Employees, Work Environment has a significant effect on Eiger Adventure Marketing Division Employee Performance, Work Discipline has a significant effect on Eiger Adventure Marketing Division Employee Performance. So that Ha is accepted and H0 is rejected. This means that Leadership Style (X1), Work Environment (X2) and Work Discipline (X3) together (simultaneously) have a significant positive effect on the Performance of Eiger Adventure Marketing Division Employees.